Effect of fibre weight fraction on the flexural and dynamic mechanical properties of arenga pinnata fibre and its hybrid composites / Abdul Hakim Abdullah ... [et al.] - Abdullah, Abdul Hakim; Amri, Amerul Farhan; Mohd Salleh, Farrahshaida; Abdul Halim, Nurul Hayati; Tharazi, Izdihar (UiTM Press for the Research Management Center (IRMI), Universiti Teknologi MARA, 2021)
This study aims to investigate the influence of fibre weight fraction on the flexural and dynamic mechanical properties of Arenga pinnata fibre and its hybrid epoxy composites. In this work, four composites configurations were fabricated using hand lay-out by varying fibre weight ratios between Arenga pinnata (AP) and glass fibre (GF); AP100% - 0%GF, AP70% - 30%GF, AP30% - 70%GF and AP0% - 100%GF, respectively. The flexural modulus indicates that the pure Arenga pinnata composites (AP100%-0%GF) are stronger than both hybrid and pure glass fibre composites (AP0%-100%GF). The increasing fibre weight fraction of glass fibre has resulted in lower flexural properties. By dynamic mechanical analysis (DMA), the storage modulus of pure Arenga pinnata composites is always higher and have better thermal resistance as compared to the pure glass fibre composites. The result indicates that Arenga pinatta fibre reinforced with epoxy composites have a great opportunity similar to that glass fibres composites counterpart in engineering application